Coagulation-flocculation followed by catalytic ozonation processes for enhanced primary treatment during wet weather conditions. (1st April 2021) - López-Vinent, Núria; Cruz-Alcalde, Alberto; Ganiyu, Soliu O.; Sable, Shailesh; Messele, Selamawit Ashagre; Lillico, Dustin; Stafford, James; Sans, Carme; Giménez, Jaime; Esplugas, Santiago; Gamal El-Din, Mohamed
Abstract: Combined sewer overflows (CSO), generated during the wet weather flow from the combination of the inflow and stormwater runoff in sewer system, result in an overflow of untreated wastewater from sewer system, which might ultimately contain different micropollutants (MPs). In this study, a coagulation-flocculation-sedimentation (CFS) pretreated CSO spiked with MPs was treated by catalytic ozonation using carbon, iron, and peroxide-based catalysts. The catalysts were characterized and their activity on MPs removal was studied at two different ozone (O3 ) doses (5 and 10 mg L −1 ). The effect of the treatment on the spiked CSO effluent was also assessed from the acute toxicity of the effluent using Microtox®, Yeast, and Macrophage cell-line toxicity assay tests. All the carbon-based catalysts showed large surface area, which was strongly influenced by the activation technique in the preparation of the catalysts. The CFS treatment strongly reduced the turbidity (≥60%) but had marginal effect on the UV254, dissolved organic carbon (DOC), and pH. Sludge Based Carbon (SBC) showed strong adsorption capacity (≥60% removal efficiency) for all MPs studied compared to other carbon and iron-based catalysts. Ozonation alone was effective for the degradation of easily oxidizable MPs (sulfamethoxazole, mecoprop, and 2, 4-dichlorophenoxyl acetic acid), achieving more than 80% degradation efficiency at 10 mg L −1 of ozone, but not effective for atrazine (≤60% degradation efficiency) at similar O3 dose. Catalytic ozonation (at 10 mg L −1 O3 dose) improved the degradation of the MPs at low catalyst dosage but higher dosage strongly inhibited their degradation. In all cases, the effluents showed negligible acute toxicity, indicating the suitability of the process for the treatment of CSO. Graphical abstract: Image 1 Highlights: Micropollutants in combined-sewage overflow (CSO) were degraded by catalytic ozonation. Coagulation-flocculation-sedimentation pretreatment improved the characteristic of CSO. Carbon-based catalysts exhibited high surface area and porosity. Treated CSO exhibited no acute/cell-line toxicity and estrogenicity.